Corrosion course teaching using a combined experimental and theoretical approach by bridging with two mandatory courses in chemical engineering program: Reaction kinetics and thermodynamics - Khadom, Anees A.; Mahdi, Mustafa S.; Mahood, Hameed B. (Education for chemical engineers, 2020)
•Corrosion, as an elective course, was related to other chemical engineering major courses.•Theoretical and practical teaching method was used to explain the role of corrosion course in chemical engineering program.•The interaction of students with the results was highly impressive and significantly affects the teaching outcomes.•The students’ performance during exams was enhanced by 15%±5%.•A questionnaire was constructed to interpret the results of current work. Corrosion course is an elective subject in Department of Chemical Engineering at College of Engineering of the University of Diyala (Iraq). It is also adopted in other departments at College of Engineering of the University of Diyala, such as, civil, mechanical and material engineering. The relation between corrosion course in the chemical engineering department and peer corrosion courses in other departments is not clear to the students. Furthermore, corrosion courses are often concentrated on electrochemistry without clear relation with some main chemical engineering courses. The present work is an attempt in the direction of connecting corrosion subject with the other major subjects of chemical engineering program. Some topics of chemical reaction kinetics and thermodynamics principles are applied to corrosion course. The corrosion inhibition behavior of mild steel in hydrochloric acid in the absence and the presence of potassium iodide as a corrosion inhibitor were selected as a case study. The influence of temperature, time and inhibitor concentration was studied using weight loss technique. Theoretical and scientific principles, experimental work, and interpretations were well clarified for the students. The interaction of students with the results was highly impressive and significantly affects the teaching outcomes. The students’ performance during exams was enhanced by 15±5 %. A questionnaire was constructed to interpret the results of current work.